2018
DOI: 10.1093/jee/toy069
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Effects of Some Insecticides on Functional Response of Habrobracon hebetor (Hymneoptera: Braconidae) When Reared on Two Lepidopteran Hosts

Abstract: The effects of four commonly used pesticides, diazinon (EC 60%), phosalone (EC 35%), fipronil (Granular formulation 0.2%), and pyriproxifen (EC 10%), on functional response of Habrobracon hebetor (Say) (Hymenoptera: Braconidae) were investigated using two lepidopteran hosts, Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) and Heliothis viriplaca (Hufnagel) (Lepidoptera: Noctuidae). Laboratory bioassays determined diazinon and fipronil as highly toxic insecticides for all developmental stages of the parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The attributes of the success of a biological control agent not only depend on its ability to manage pests but also on its compatibility with other pest management methods, especially chemical management. 63 The importance of bio-control agents in IPM has resulted in the development of various methods for estimating the effects of insecticides on the bio-control agents. The degradation of insecticides due to rainfall, high temperature, sunlight, etc., alters the target concentrations of the insecticides, thereby resulting in lethal as well as sublethal concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The attributes of the success of a biological control agent not only depend on its ability to manage pests but also on its compatibility with other pest management methods, especially chemical management. 63 The importance of bio-control agents in IPM has resulted in the development of various methods for estimating the effects of insecticides on the bio-control agents. The degradation of insecticides due to rainfall, high temperature, sunlight, etc., alters the target concentrations of the insecticides, thereby resulting in lethal as well as sublethal concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitoids with higher searching efficiency and lower handling time are considered to be better bio-agents. 63,81 The coefficient of attack rate is positively correlated with searching efficiency and negatively with the handling time of a bio-control agent, thereby resulting in searching efficiency and handling time being maximum and minimum, respectively. 23 This further resulted in increasing the asymptote of the curve, thereby indicating a higher attack rate by a bio-agent on the targeted host/prey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result differed from other studies such as Rashidi et al which found that sublethal doses of four pesticides negatively affected the control efficiency of Habrobracon . Hebetor [ 47 ]. It might due to the weak toxicity of SYP-9625 against N .…”
Section: Discussionmentioning
confidence: 99%
“…: Braconidae) (Rezaei et al, 2014), Habrobraon hebetor Say, 1836 (Hym. : Braconidae) (Abedi et al, 2012, Mahdavi et al, 2013, Rashidi et al, 2018, Dolichogenidea tasmanica (Cameron, 1912) (Hym. : Braconidae) (Paull et al, 2014), and Eretmocerus mundus Mercet, 1931 (Sohrabi et al, 2014) have been reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%